Politically Motivated Violence: The Safety and Security concerns of people with visual impairment - Munemo, Emmanuel (Advances in Social Sciences Research Journal, 2018)
The purpose of this study was to establish the extent to which safety and security concerns of people with visual impairment were catered for when politically motivated violence erupted. High stakes in elections, render the electoral process to serious risks of politically motivated violence. People with visual impairment may get maimed, killed or left with multiple disabilities. Politically motivated violence exposes voters and potential voters with visual impairment to serious safety, security and health concerns. For people with visual impairment especially the blind finding a safe place to take refuge can be a daunting task. This study used the qualitative paradigm, and was accordingly informed by the interpretative design. Opportunity sampling was made use of. Data was generated through interviews. The study found out that the safety and security of people with visual impairment was highly compromised in the event of violence. It was established that people with visual impairment exaggerated the potential danger they faced. It was also found out that sometimes police and security forces were often implicated as interested parties and active participants. It was therefore established that there were no guarantees of the safety and security of people with visual impairments. This study recommended that Electoral Authorities put in place strategies to guarantee the protection of people with visual impairment in the event of violence.